التحكيم بين الوكالة والولاية وتطبيقاته في المالية الإسلامية : دراسة فقهية مقارنة مع القانون السوري - عيسى، عبد الحنان بن محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The study discusses the concept of arbitration, its legitimacy, and its importance in Islamic jurisprudence and the Syrian law. The study defines arbitration, whether it is Proxy or Guardianship, the nature of the arbiter's function since ambiguity surrounds it and leads to vagueness in the understanding of those who work in the field including the jurists of secular law and Muslim jurists. The study also sheds light on the injunctions of both proxy and guardianship and the distinguishing injunctions and parameters that sets arbitration apart. Moreover, it discusses the adaptation of the nature of arbitration and the function of the arbiter. The implications resulting from adapting the nature of the arbiter's function in terms of appointment, termination, mandate, and the progress of the arbitration process and the issuance of the arbiter's decision are also examined. The last chapter of the study reviews the applications of arbitration in Islamic finance through the experience of the International Islamic Centre for Reconciliation and Arbitration (IICRA) in Dubai and the role of the arbiter in readapting the contractual obligations. The researcher adopted the methods of inductive, analytical, and comparative. The study finds that arbitration is the best mechanism to resolve the disputes of Islamic financial institutions, since the parties to the dispute can choose Sharia as the law to be applied to the dispute, which is in line with the nature upon which these institutions are established.